2022
DOI: 10.1111/1754-9485.13449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating delays in patients treated with post‐operative radiation therapy for head and neck squamous cell carcinoma

Abstract: Introduction: Delays in commencing post-operative radiation therapy (PORT) and prolongation of overall treatment times (OTT) are associated with reduced overall survival and higher recurrence rates in patients with head and neck squamous cell carcinoma (HNSCC). The objective of this study was to evaluate treatment delays, factors contributing to those delays and to explore strategies to mitigate them. Methods: This retrospective study included patients with mucosal HNSCC at Townsville University Hospital treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Other variables associated with delays in our cohort with univariate analysis included stage III/IV cancer and PORT at another institution, consistent with prior studies 33 . The association between outside facilities and delays suggests that fragmentation of care is a contributing factor.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Other variables associated with delays in our cohort with univariate analysis included stage III/IV cancer and PORT at another institution, consistent with prior studies 33 . The association between outside facilities and delays suggests that fragmentation of care is a contributing factor.…”
Section: Discussionsupporting
confidence: 86%
“…34 While other studies have found the length of postoperative hospital stay to be associated with delays in treatment, it did not modify the risk of PORT delay for the present cohort. 20,33 These findings, while important, do not provide meaningful information in the preoperative setting that can help guide earlier patient intervention. Furthermore, distinguishing variables that may mediate delays through association, such as length of stay, from variables that directly moderate delays, such as social support, is important when creating targeted interventions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…44,45 A time delay in one or more steps on the pathway to therapy may result in an eventual delay in patient receiving ultimate care. 46 At the patient level, those with advanced disease or underlying medical complications may require more postoperative recovery time for wounds to heal. The time required for wound healing is patient-specific and involves many factors, including presence of chronic comorbidities such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patient's access to radiotherapy maybe disrupted by issues such as travel distance and insurance referral 44,45 . A time delay in one or more steps on the pathway to therapy may result in an eventual delay in patient receiving ultimate care 46 . At the patient level, those with advanced disease or underlying medical complications may require more postoperative recovery time for wounds to heal.…”
Section: Discussionmentioning
confidence: 99%